Analisis Pola Asuh Orangtua Terhadap Sosial Emosional Generasi Alpha - Shafa Salsabil; Rika Partika Sari; Ranny Fitria Imran (Early Childhood Research and Practice, 2026)
This study aims to determine how parenting patterns of parents towards the social emotional of the alpha generation. This study is a qualitative study. The study was conducted in the RT.01 RW.05 Kel. Talang Benih. The researcher used the theory of Yaumil Achir, CA which discusses three parenting patterns, namely authoritarian parenting, democratic parenting and permissive parenting. The results of the study regarding authoritarian parenting patterns are no longer widely used by parents who are the subjects of the study. The democratic parenting pattern that almost all parents apply can be seen from the support and opportunities to learn and gain experience that supports the development of children's social emotions. And there are no parents who are the subjects of the study who use permissive parenting patterns. It can be concluded that the parenting patterns of parents who have alpha generation children apply democratic parenting patterns that have a good effect on the social emotions of alpha generation children. Another factor that influences children's social emotions is the environment.